The effect of transformation rate in hantavirus infection model / Norhuda Mohammed, Asyura Abd Nassir and Nazirah Ramli - Mohammed, Norhuda; Abd Nassir, Asyura; Ramli, Nazirah (2014)
Hantaviruses are severe viruses that were namely based on infected mice found near Korea's Hantaan River. These viruses are carried by rodents such as birds and mice without harming the hosts themselves, but can cause fatal diseases to human. A model showing the spread of Hantavirus infection through rodents namely as AK model has been proposed by Abramson and Kenkre. Many studies have investigated the model but none look into the effect of changes in the parameter of AK model. In this paper, we investigate the effect of small changes of transformation rate to the number of infected mice in the AK model. The birth rate, natural death rate and carrying capacity are considered as fixed with values 1, 0.5 and 20 respectively. The Rungge-Kutta 4th order method has been applied to solve the AK model with changes in transformation rate by using Matlab programming. The results show that the small changes in transformation rate will lead to the changes in the number of infected mice.